High Performance LSC Infiltrated LSCF Oxygen Electrode for High Temperature Steam Electrolysis Application. Issue 2 (17th January 2019) - Vibhu, V.; Yildiz, S.; Vinke, I. C.; Eichel, R.-A.; Bassat, J.-M.; de Haart, L. G. J.
Abstract : This work is focused on La0.6 Sr0.4 CoO3-δ (LSC) infiltrated La0.58 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) oxygen electrode for high temperature steam electrolysis aimed at efficient hydrogen production. In this respect, first the chemical and structural stability of both LSCF and LSC materials are investigated as a function of temperature under air and oxygen. The electrochemical performance of LSC infiltrated LSCF oxygen electrode is then investigated for steam electrolysis and compared with conventional LSCF electrode. The symmetrical half-cell as well as single cell containing LSCF oxygen electrode with and without LSC infiltration are characterized using electrochemical impedance spectroscopy in the temperature range 700–900°C. It is observed that the symmetrical cell as well as single cells with LSC infiltrated LSCF electrode performs better than the conventional LSCF electrode. The degradation experiments were performed with the symmetrical cells under polarizations. Post-test analysis using SEM-EDX was performed to investigate the changes of electrode and electrode/electrolyte interface microstructures.